2017
DOI: 10.1007/s00192-017-3513-2
|View full text |Cite
|
Sign up to set email alerts
|

Use of an iPad™ application in preoperative counseling for pelvic reconstructive surgery: a randomized trial

Abstract: The addition of a POP-based iPad™ application to the informed consent process for POP surgery did not improve patient comprehension immediately postcounseling and resulted in poorer retention of information 6 weeks after surgery compared with SVC alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 13 publications
0
20
1
Order By: Relevance
“…This randomized controlled trial showed that the addition of an easy-to-ready patient education card enhances patient recall of the planned procedure before surgery. This finding is in contrast to many previous studies that had not demonstrated improvement in patient scores with the use of more sophisticated patient education tools 11,14,15 . Some unique features of the patient education card used in this trial were its concise nature, readability, and format, which allowed patients to have it with them at all times.…”
Section: Discussioncontrasting
confidence: 80%
“…This randomized controlled trial showed that the addition of an easy-to-ready patient education card enhances patient recall of the planned procedure before surgery. This finding is in contrast to many previous studies that had not demonstrated improvement in patient scores with the use of more sophisticated patient education tools 11,14,15 . Some unique features of the patient education card used in this trial were its concise nature, readability, and format, which allowed patients to have it with them at all times.…”
Section: Discussioncontrasting
confidence: 80%
“…Across the above categories, a total of 43 interventions (72%) were noninteractive and 17 (28%) were interactive. Eight of the interactive interventions included test/feedback or teach-back components, including 1 audiovisual intervention, 39 5 digital interventions, 72,76…”
Section: Resultsmentioning
confidence: 99%
“…Most studies did not specify participants' health literacy level (88%, 46/52) or race/ethnicity (79%, 41/52), and 4 studies explicitly excluded participants with low literacy levels. 38,72,73,75 Twenty-four studies (46%) included proficiency in the study language in their eligibility criteria, and only 3 specified inclusion of participants requiring interpreters. 37,57,71 Education was reported in a variety of ways, including the percentage of participants having completed certain school levels or mean education in years (Tables 1-6).…”
Section: Study and Participant Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…audiovisual materials, in addition to SIC, may reinforce knowledge without increasing patient anxiety [6]. Video media are useful for this purpose, and they are often used in trials [8][9][10]. Portable tablets and similar electronic devices allow clinicians to enhance information in a wide variety of situations.…”
Section: Original Articlementioning
confidence: 99%